A Review of the Book Nashat al-Masrah in the East (The Emergence of Theater in the East) - Farhad Rajabi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The art of play is the result of human social life, more than any other type of art in relation to social man, and accordingly, its connection with the new civilization can be emphasized more than other components. In the new era, the play is one of the most important topics for critical discussions, whether as a text or as a collection of narratives performed by actors on stage to the extent that the critical and historical books of this type of art have a wide range of the oldest types of art. One of the most recent works of this kind is Nashat 'al-Masrah fi al-Mashreq, (The Emergence of Theater in the East), whose author has studied the origin and evolution of this art in the Orient, focusing on Lebanon and Syria, Turkey and Iran. The article intends to provide a critical reading of it by adopting a descriptive method, and the results show that although the value of the book in question is small, the author has been able to use accurate methods in reviewing the evolution of the work as a historical-analytical book by using reliable documents and sources.